PROMOTING STUDENTS’ CONFIDENCE THROUGH VIDEO PROJECT-BASED LEARNING - Via Nandiana; Alan Jaelani; Nurul Afiyattena (Journal of English Language Learning, 2021)
Students require confidence in order to use language they are learning, yet self-confidence remains a challenge for them in language learning. This research examines Video Project-Based Learning (VPBL) which is a video learning method as an educational process of delivering knowledge and skills. In this study, the researchers focus on students’ perception on the use of project-based learning using video as a method to promote students’ confidence in learning English. The study was conducted at the fifth semester of 2019-2020 academic year in English Education Department of a university in Bogor. The data was collected by qualitative approach with open-ended questionnaire and semi-structed interview for ten students as the respondents. This research found that the use of VPBL can facilitate student information processing faster, retain knowledge and remember materials accurately, encourage students to apply and develop their creativity in learning, promote students’ confidence in speaking skills and enhance speaking skills with their own understanding and creativity with the lesson. This research advises taking a broader view of students' self-confidence as the implication of video project-based learning in individual project is really needed.